Examining the Role and Perception of Nepali Peacekeepers in Nepal’s Foreign Policy Narratives - Bista, Prakash; Chapagain, Dip Mala (Unity Journal, 2024)
In the mid of July, a few Members of the Parliament proposed the idea of downsizing the Nepali Army as one of the measures to decrease public spending. But this is not the first time that such debate has stirred in the Nepalese political stratum. The topic of downsizing the Nepalese Army has been reiterated from time to time in the higher echelons of the Nepali government, most notably following the Comprehensive Peace Accord (CPA). At the national level, The Nepal Army as an institution has been deployed since centuries for to accomplish a wide array of functions. On the international front, the Nepbat has been deployed in UN Peacekeeping missions since 1958 in war-prone regions and is largely regarded as a highly competent battalion of proven caliber. Nepal Army's global exposure and experience as such have also refined the institution's conflict resolution and crisis management skills. But despite such positive global acknowledgment and the rich experience that the Nepal Army has garnered, the deliberations regarding the utilization of their insights and experiences in Nepal’s foreign policy discourse seem to have been kept at an arm's length. To identify the role of the Nepali Army in promoting the value of world peace as enshrined in the Nepalese Constitution, this article has intended to investigate the level of recognition and influence of their insights in Nepal's foreign policy discourse. This qualitative study based on both primary and secondary data and process tracing and interview methods, identified that the imbalances in the state's priorities have led to the skills of Nepali peacekeepers from their global exposure being kept under the radar. The study has then suggested some of the possibilities for incorporating military expertise into Nepal's foreign policy discourse.